Karyotype diversity and chromosomal organization of repetitive DNA in Tityus obscurus (Scorpiones, Buthidae) - Bruno Rafael Ribeiro de Almeida; Susana Suely Rodrigues Milhomem-Paixão; Renata Coelho Rodrigues Noronha; Cleusa Yoshiko Nagamachi; Marlyson Jeremias Rodrigues da Costa; Pedro Pereira de Oliveira Pardal; Johne Souza Coelho; Julio Cesar Pieczarka (BMC Genetics, 2017)
Abstract Background Holocentric chromosomes occur in approximately 750 species of eukaryotes. Among them, the genus Tityus (Scorpiones, Buthidae) has a labile karyotype that shows complex multivalent associations during male meiosis. Thus, taking advantage of the excellent model provided by the Buthidae scorpions, here we analyzed the chromosomal distribution of several repetitive DNA classes on the holocentric chromosomes of different populations of the species Tityus obscurus Gervais, 1843, highlighting their involvement in the karyotypic differences found among them. Results This species shows inter- and intrapopulational karyotype variation, with seven distinct cytotypes: A (2n = 16), B (2n = 14), C (2n = 13), D (2n = 13), E (2n = 12), F (2n = 12) and G (2n = 11). Furthermore, exhibits achiasmatic male meiosis and lacks heteromorphic sex chromosomes. Trivalent and quadrivalent meiotic associations were found in some cytotypes. In them, 45S rDNAs were found in the terminal portions of two pairs, while TTAGG repeats were found only at the end of the chromosomes. In the cytotype A (2n = 16), the U2 snRNA gene mapped to pair 1, while the H3 histone cluster and C 0 t-1 DNA fraction was terminally distributed on all pairs. Mariner transposons were found throughout the chromosomes, with the exception of one individual of cytotype A (2n = 16), in which it was concentrated in heterochromatic regions. Conclusions Chromosomal variability found in T. obscurus are due to rearrangements of the type fusion/fission and reciprocal translocations in heterozygous. These karyotype differences follow a geographical pattern and may be contributing to reproductive isolation between populations analyzed. Our results also demonstrate high mobility of histone H3 genes. In contrast, other multigene families (45S rDNA and U2 snRNA) have conserved distribution among individuals. The accumulation of repetitive sequences in distal regions of T. obscurus chromosomes, suggests that end of chromosome are not covered by the kinetochore.